Applied regression analysis for business and economics - Dielman, Terry E (Boston, 1991)
This text takes an applied, modern approach to regression analysis by using real world data sets and extensive computer output to emphasize modelling, interpretation of results, and decision making rather than formulas and number crunching. Students do not need facility in matrix algebra to learn interpretation skills and the use of computer output in the exercises and problems, as matrix algebra is not used to develop the notation. Real world examples are used throughout the text to demonstrate practical use of methods, with data taken from such sources as Forbes, U.S. News and World Report and other journals. SAS and Minitab output for many examples and exercises is included.
Keywords: Economics statistical methods